2014
DOI: 10.1089/jmf.2012.0262
|View full text |Cite
|
Sign up to set email alerts
|

Feijoa sellowianaBerg Fruit Juice: Anti-Inflammatory Effect and Activity on Superoxide Anion Generation

Abstract: Feijoa sellowiana Berg var. coolidge fruit juice was studied in vivo for the anti-inflammatory activity by carrageenin-induced paw edema test and in vitro for the effects on superoxide anion release from neutrophils in human whole blood. The fruit juice was analyzed by the high-performance liquid chromatography method, and quercetin, ellagic acid, catechin, rutin, eriodictyol, gallic acid, pyrocatechol, syringic acid, and eriocitrin were identified. The results showed a significant anti-inflammatory activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 32 publications
0
24
0
1
Order By: Relevance
“…The operating conditions were optimized to obtain the highest signal-to-noise ratio for 7 Li, 59 Co, 115 In and 238 U with 140 Ce, 16 O/ 140 Ce < 2.5% and 140 Ce and 16 O < 5%. In particular, we used: RF power, 1500 W; plasma gas flow rate, 15 L min −1 ; auxiliary gas flow rate, 0.9 L min −1 ; carrier gas flow rate, 1.1 L min −1 ; helium collision gas flow rate, 4 mL min −1 ; spray chamber temperature, 2 ∘ C; sample depth, 9 mm; sample introduction flow rate, 1 mL min −1 ; nebulizer pump, 0.1 RPS; extract lens 1 voltage, 1.5 V. The instrument was used in no-gas mode for Mn, Pb, Zn, Mg, Ca, Na, K, and in helium mode for Ni, As, Se, Cd, Fe, Cu, to remove spectral interference.…”
Section: Icp-ms Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The operating conditions were optimized to obtain the highest signal-to-noise ratio for 7 Li, 59 Co, 115 In and 238 U with 140 Ce, 16 O/ 140 Ce < 2.5% and 140 Ce and 16 O < 5%. In particular, we used: RF power, 1500 W; plasma gas flow rate, 15 L min −1 ; auxiliary gas flow rate, 0.9 L min −1 ; carrier gas flow rate, 1.1 L min −1 ; helium collision gas flow rate, 4 mL min −1 ; spray chamber temperature, 2 ∘ C; sample depth, 9 mm; sample introduction flow rate, 1 mL min −1 ; nebulizer pump, 0.1 RPS; extract lens 1 voltage, 1.5 V. The instrument was used in no-gas mode for Mn, Pb, Zn, Mg, Ca, Na, K, and in helium mode for Ni, As, Se, Cd, Fe, Cu, to remove spectral interference.…”
Section: Icp-ms Analysismentioning
confidence: 99%
“…3 This plant is extremely drought tolerant and grows abundantly under semiarid conditions; 4 in fact, a common feature of the areas where the plant grows is a more or less marked degree of aridity to which the plant has adapted as a result of its photosynthetic metabolism. 5 The cactus pear grows in all parts of the American continent, from southern Canada to southern Argentina, and in the course of time has been cultivated in different areas of Africa and Europe, especially in the Mediterranean area, like some other tropical fruits, [6][7][8] becoming a significant local crop. In particularly, Sicily (Italy) is the second-largest producer of Opuntia fruits in the world, 9,10 and the typical Sicilian variety of prickly pear, Opuntia ficus indica L. Miller, known as a symbol of this region, has gradually obtained increasing economic importance in agriculture, food and the cosmetics industry.…”
Section: Introductionmentioning
confidence: 99%
“…Feijoa fruit present translucent jelly-like pulp, with sweet acidulated flavor, and unique aroma (MATTOS, 1990). Due to its chemical composition, several studies have demonstrated the pharmacological properties of the species (WESTON, 2010), such as antibacterial, anti-inflammatory and antioxidant activities (KELES et al, 2012;MONFORTE et al, 2014); and to their antifungal activity against Candida glabrata, which is resistant to fluconazole (MACHADO et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Fruit extracts have been shown to modulate the immune system significantly even within a day of treatment (11, 13). Nevertheless, studies with long term treatments, e.g., of 33 days (12) to 70 days (10) also provide similar evidence of immunomodulatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Feijoa sellowiana Berg var. coolidge fruit juice consumption was shown to have anti-inflammatory activity on edema-induced mice within first hour of treatment (13) while agipenin, a natural flavonoid reduced neuroinflammation by protection against damage from dendritic cells stimulated T cells in experimental autoimmune encephlalomyelitis mouse models (14). Dietary polyphenols were found to exert a regulatory role on dendritic cell function.…”
Section: Introductionmentioning
confidence: 99%